FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS TENAGA KERJA KARYAWAN PEMANEN KELAPA SAWIT DI PT. ALAM JAYA PERSADA FACTORS AFFECTING WORK PRODUKTIVITY OF OIL PALM HERVESTING EMPLOYEE IN PT. ALAM JAYA PERSADA - Sesilia Abdiyani; Sri Ngapiyatun; Faradilla (JURNAL AGRIMENT, 2019)
Harvesting process is very important on determining the quality of CPO produced so that it can increase revenue or reciprocity toward company's development. This encourages researcher to analyze what factors influence the productivity of oil palm harvesters. This study used sample of 20 people. Sample was determined by using Non Probability Sampling technique with census method or saturated sample which used all the population as sample because the population was less than 30 people. The data were collected by questioner and interviewing the chosen respondents. Variables in this study were age (X1), education (X2), work tenure (X3), number of dependents (X4) and the dependent variable was employee's work productivity (Y). The Data ws analyzed by using multiple linear regression with effective contribution test and coefficient of determination test. The result showed that age and education factors had positive affect toward employee's work productivity. Beside of that, work tenure and number of dependents had negative effect on employee's work productivity and the most dominant contribution among the four factors was the number of dependents. In addition, the value of R square or the coefficient of determination showed that factors of age, education, years of service and the number of dependents together affected work productivity by 41.7% and the remaining 58.3% were influenced by other factors outside the study.